2015
DOI: 10.1111/1556-4029.12739
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Age Estimation Using Thin‐Slice Multidetector CT of the Clavicular Epiphyses Among Adolescent Western Chinese

Abstract: Reaching the age of 18 years is the most significant step for criminal proceedings in China. In this study, a population of 752 individuals was recruited to clarify how strong the chronological age relates to clavicular ossification status revealed by CT scans with 1 mm slice thickness in the West China Han population. Finally, the epiphysis was observed to commence fusion in females at 16.28 years and 16.74 years in males and be fully ossified by 25.97 years in females and 25.81 years in males. These findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 19 publications
3
8
0
Order By: Relevance
“…Thus, it is better to provide age intervals instead of point estimates. In the present study, we found that 100% of subjects with stage IV and V ossification were ≥18 years similar to Pattamapaspong et al (15) and Zhang et al (16). Our study showed that subjects of both sexes with stage III B have 0% probability to be <18 years, and those with stage II have a probability of 79.3% to be <18 years.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Thus, it is better to provide age intervals instead of point estimates. In the present study, we found that 100% of subjects with stage IV and V ossification were ≥18 years similar to Pattamapaspong et al (15) and Zhang et al (16). Our study showed that subjects of both sexes with stage III B have 0% probability to be <18 years, and those with stage II have a probability of 79.3% to be <18 years.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, the ossification stages of medial clavicular epiphysis were defined using a modified version of the Schmeling classification (7), which is a widely accepted system (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Previous studies showed that an individual can be estimated to be ≥18 years when complete ossification of epiphyseal cartilage (stage IV, V) is observed (8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We think that a change from stage 5 to stage 4 is possible and that the acceptability of the study data of Pattamapasong et al [33] to forensic age estimation should be discussed. Zhang et al [34] evaluated the clavicular medial epiphyses according to the four staging method, which were outdated already with the addition of a stage 5 by Schmeling et al [18] and especially by the introduction of substaging of the phases 2 and 3 by Kellinghaus et al [29]. Because they conducted evaluations according to the four staging method, they could not observe the difference of age minima between the stages 4 and 5.…”
Section: Discussionmentioning
confidence: 99%
“…Some age estimation studies have adopted an anatomical perspective by assessing ossification by direct skeletal inspection [7][8][9][10][11][12][13][14], whereas other studies have adopted a radiological approach by using technologies such as X-ray [15][16][17][18][19][20][21][22], CT [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], ultrasonography [35,[39][40][41], or magnetic resonance imaging [42,43]. CT imaging and projection radiography have significant advantages and are the modalities suggested by AGFAD [6].…”
Section: Introductionmentioning
confidence: 99%